Percutaneous Fat Transfer to Treat Knee Osteoarthritis Symptoms: Preliminary Results - Adriani, Ezio; Moio, Mariagrazia; Di Paola, Berardino; Salustri, Walter; Alfieri, Andrea; Parisi, Paola; Ruggiero, Marco; Borab, Zack; Carlesimo, Bruno (Joints, 2017)
Purpose This study aims to evaluate the safety and efficacy of autologous aspirated and purified fat tissue injected percutaneously into the knee joint for the treatment of symptomatic osteoarthritis (OA).Methods We reviewed 30 patients, who received an autologous percutaneous fat injection for the treatment of knee OA, from January 2012 to March 2015. Mean patients' age was 63.3 ± 5.3 years (range, 50–80 years). Body mass index was 25.1 ± 1.7. Clinical evaluation was based on pain visual analog scale (VAS) and WOMAC score for functional and subjective assessment. We also noted the adverse reactions and the consumption of nonsteroidal anti-inflammatory drugs in the posttreatment period.Results All patients reported improvements with respect to pain: average VAS was 7.7 ± 1.2 at baseline, 5.2 ± 0.2 at 1-month follow-up, and 4.3 ± 1 at 3-month follow-up. A slight deterioration (5.0 ± 1.1) was evidenced at 1 year. Total WOMAC score was 89.9 ± 1.7 at baseline, 66.3 ± 1 at 1 month, 68.6 ± 1.7 at 3 months, and 73.2 ± 1.8 at 12 months of follow-up.Conclusion Our preliminary findings suggest that autologous percutaneous fat injections are a valid treatment option for knee OA.Level of Evidence Level IV, therapeutic case series.
Keywords: fat tissue; knee; osteoarthritis; injections; aspirate